Predicting progressive collapse for multi storey precast concrete building with different structural systems - Wong, Gilbert Pak Kai (Universiti Malaysia Sarawak, UNIMAS, 2012)
Recent historic events have shown that buildings that are compliance to conventional building codes design are not necessarily able to resist the progressive or disproportionate collapse that generally occur due to missing, damage or collapse of structural elements. For example, a collapse of slender and unbraced columns in a structure. The well known collapsed building in the world was the World Trade Center, which collapsed in September 2001 due to progressive collapse. Hence, a three dimensional multi storey precast building with different structural systems with "missing column" concept is investigated. The model building is based on the actual building of Police Housing Flat in Stutong district, Kuching. The study is based on linear static analyses using software abaqus 6.11 with non linear material properties.